Adaptability of six native forest tree species to degraded lands in Pucallpa, Peruvian Amazon - Soudre, M.; Ricse, A.; Carbajal, Y.; Kobayashi, S.; Sabogal, C.; Alegre, J. (Center for International Forestry Research, 2001)
Preliminary results of a field study in Pucallpa, Peruvian Amazon, to determine the establishment of six native forest tree species of economic value on degraded areas abandoned after intensive past agricultural use are reported. Study sites were on slash-and-burn farms partially covered with abandoned agricultural areas on Ultisols dominated by invading vegetation mainly composed of Imperata brasiliensis, Rottboellia cochinchinensis and Baccharis floribunda. Tree species used in the trials were: Schizolobium amazonicum, Tabebuia serratifolia, Calycophyllum spruceanum, Terminalia oblonga, Amburana cearensis and Cedrelinga catenaeformis. These six species were planted in three degraded habitats characterised by the presence of one of the above weed species. After 13 months, Schizolobium amazonicum was the best adapted in the three experimental treatments, followed by Tabebuia serratifolia and Calycophyllum spruceanum. Habitats dominated by Baccharis floribunda offered comparatively better conditions for tree establishment and initial growth.